Financial stress spillovers across the banking, securities and foreign exchange markets - Apostolakis, George; Papadopoulos, Athanasios P. (Journal of Financial Stability, 2015)
In this paper, we measure the interdependence of three financial stress sub-indices (banking, securities and foreign exchange) for the major advanced economies during the 1981–2009 period using a single index based on the generalized variance decompositions developed by Diebold and Yilmaz (2012). We present spillover tables and indices that demonstrate financial stress innovations to and from other indices, in addition to spillover plots that show the dynamics of stress. Furthermore, we examine the relationship between financial stability and macroeconomic fundamentals by investigating the effects of financial stress on growth and on price levels. We proxy financial stability and monetary stability with a financial stress index (FSI) and a consumer price index (CPI), respectively, and examine their interdependence. Our findings indicate that the securities markets are the main net transmitters of stress to the other markets. In addition, up to 42.8% of the forecast error variance in all the markets examined emanates from stress spillovers. Finally, our findings highlight the interrelationship of financial and monetary stability.